(untitled) (Research, Society and Development, 2020)
Objectives: to verify the prevalence of body regions most affected by the symptoms of musculoskeletal disorders in nursing professionals working in medical clinic services and to discuss the occurrence of symptoms of musculoskeletal disorders self-reported by these professionals, from the perspective of workers’ health. Method: This is a descriptive cross-sectional study that sought to analyze the symptoms of musculoskeletal disorders in 81 nursing professionals who work at a University Hospital in the city of Rio de Janeiro. The sociodemographic labor questionnaire and the Nordic Musculoskeletal Questionnaire were used. Results: it showed in the age group that 38.2 are over 41 years old, 81.5% are female, with a predominance of 77.8% of nursing technicians and assistants. In the Nordic Musculoskeletal Questionnaire, the presence of musculoskeletal symptoms with a predominance in the neck region was verified 39.5%, followed by the lower back, ankles and or feet with 38.3% in the last 12 months, 22.2% of the interviewees were prevented from carrying out their activities and 33.3% had consultations due to musculoskeletal symptoms. It was observed that 19.8% of the interviewees reported musculoskeletal symptoms in the lower back and 18.5% in the ankles / feet in the last seven days. Conclusion: At the end of the study, it can be seen that nursing workers indicated a prevalence of pain, tingling and or numbness in the regions of the neck, lower back, ankles / feet in a period of 12 months and in the last seven days in the lower part of the back and ankles / feet, in view of the results, it is necessary to take preventive and promotional measures that guarantee better working conditions for the nursing team, in order to reduce the risks for the development of musculoskeletal symptoms arising from their work environment.